Comparison of patients' and general practitioners' evaluations of general practice care. Issue 4 (1st December 2002) - Jung, H P; Wensing, M; Olesen, F; Grol, R
Abstract : Objectives: To compare patients' and general practitioners' (GPs') evaluations of the quality of general practice care. Design: Written surveys among patients and GPs. Setting: General practice in the Netherlands. Subjects: 1772 patients (from 45 GPs) and a random sample of 315 GPs. Main outcome measures: Patients' and GPs' evaluations of 23 aspects of general practice care and GPs' perceptions of patients' evaluations using a 5 point scale. Results: The response rate was 88% in the patient sample and 63% in the GP sample. The patients' ratings of care were significantly more positive (mean 4.0) than those of the GPs (mean 3.7) as well as GPs' perceptions of patients' evaluations (mean 3.5) (p<0.001). The overall rank order correlations between the patients' evaluations, GPs' evaluations, and GPs' perceptions of the patients' evaluations were 0.75 or higher (p<0.001). Patients and practitioners gave the most positive evaluations of specific aspects of the doctor-patient relationship ("keeping patients' records and data confidential", "listening to patients", and "making patients feel they had enough time during consultations") and aspects of the organisation of care ("provide quick service for urgent health problems" and "helpfulness of the staff (other than the doctor)"). The aspects of care evaluated least positively by patients as well as by GPs were other organisational aspects ("preparing patients for what to expect from specialist or hospital care" and "getting through to practice on the telephone"). Conclusions: GPs and patients have to some extent a shared perspective on general practice care. However, GPs were more critical about the quality of care than patients and they underestimated how positive patients were about the care they provide. Furthermore, specific aspects of care were evaluated differently, so surveys and other consultations with patients are necessary to integrate their perspective into quality improvement activities.